Great Bear Lake and Great Slave Lake Bathymetry - Kheyrollah Pour, Homa; Attiah, Gifty (Borealis, 2022)
This dataset contains bathymetry data for Great Bear Lake and Great Slave Lake, Northwest Territories, Canada. Data is in TIFF file format at 10m intervals. The bathymetries are created based on the below references: Johnson, L. (1993). Great Bear Lake. In R. J. Allan (Ed.), The Book of Canadian Lakes (Monograph Series No. 3) (pp. 549-559). Canadian Association on Water Quality. Schertzer, W., Rouse, W., & Blanken, P. (2000). Cross-lake variation of physical limnological and climatological processes of Great Slave Lake. Physical Geography, 21 (5), 385-406. doi:10.1080/02723646.2000.10642716